CircNup188/miR-760–3p/Map3k8 axis regulates inflammation in cerebral ischemia. (August 2022) - Zhang, Hui; Deng, Jian; Huang, Kangling; He, Yibo; Cai, Zhili; He, Yitao
Abstract: Introduction: Cerebral ischemia is a serious acute disease with high mortality and disability rates. circRNAs are associated with cerebral ischemia inflammation and can be used as therapeutic targets. We aimed to investigate circNup188/miR-760–3p/Map3k8 role in inflammation during cerebral ischemia. Methods: According to the sequencing results of previously published, signaling pathways and circRNAs related to inflammation were screened and looped for verification. In vitro OGD/R cell model was constructed to detect OGD/R effects on PC12 cell viability, apoptosis, inflammatory cytokines TNF-α, IL-1β and IL-6. qRT-PCR assessed circRNAs, circNup188 bound miRNAs, and four mRNAs associated with inflammation and brain diseases expressions. p65 and IkB-α and their phosphorylated proteins in NF-κB pathway and Map3k8 expressions were assessed by Western blot. Results: KEGG analysis revealed MAPK and NF-kappaB signaling pathways played a vital role in it, and were classic inflammatory pathways. circNup188, circU2, and circCnot2 were verified to be the loop structure. circNup188 might play an essential role in OGD/R cell model. Regulating circNup188 expression could affect OGD/R cells function. In addition, miR-760–3p might play a vital role in OGD/R cell model. Moreover, circNup188 regulated cerebral ischemia by sponging miR-760–3p. miR-760–3p might be involved in inflammation in OGD/R cell model by regulating Map3k8 to activate the NF-κB pathway. Conclusions: circNup188 might up-regulate Map3k8 expression through sponging miR-760–3p and then activate NF-κB pathway, which was involved in cerebral ischemia development. This study provided a new target for cerebral ischemia treatment. Highlights: Regulating circNup188 expression could affect OGD/R cells function. CircNup188 regulated cerebral ischemia by sponging miR-760–3p. MiR-760–3p might be involved in inflammation in OGD/R cell model by regulating Map3k8 to activate the NF-κB pathway.